Comparative feeding value of grain sorghum and corn in beef cattle diets - G. Goldy; K. Bolsen; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1987)
Homozygous yellow endosperm grain sorghum had no advantage in feeding value over heterozygous yellow endosperm hybrids (P>.05). A heterozygous yellow endosperm hybrid, Funk's 550, had larger kernels (P<.001) and when dry rolled, produced more fine particles (P<.01). This may explain its trend toward improved feed efficiency, higher DM digestibility, and greater in vitro VFA production compared with the other dry processed grain sorghum hybrids tested. Our results do not support the traditional 12 to 16% price discount for grain sorghum relative to corn.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Grain sorghum; Corn; Diet